The Role and Function of the Audit Committee - Bender, Ruth (Cranfield University, 2005)
There is no universal standard for the way in which audit committees work. Although broadly they covered the same activities, the number of formal meetings of companies reviewed ranged between 3 and 13 in the year. The time taken per meeting also differed considerably. Although all audit committee members must be independent non-executives, practice differs considerably as to whether the company chairman and/or the CEO regularly attend audit committee meetings. The documentation supporting audit committee work needs to be managed carefully to ensure that the committee members are well-informed, but are not so overloaded with information that key points are missed. Dealing with regulatory matters takes a great deal of audit committee time. It can be useful to schedule a ‘white space' meeting to discuss broader risk issues. Having multiple directorships, and being able to compare practices in different companies, is an advantage to audit committee members both in evaluating the performance of their committees and in providing strategic advice. Audit committee evaluation takes place in a variety of formal and informal ways, including interviews and questionnaires, administered internally and by external professionals. It is very important to non-executives that they feel that they can trust the company's executives. The corollary to this is that in situations where the executives are considered less trustworthy, governance might be difficult as well-qualified potential non-executives might be reluctant to join the board. There appears to be an expectations gap between how the audit committees see their regulatory role and how this is perceived by the media. For example, some parts of the media appear to see the audit committee role as the prevention and detection of fraud. This view sits uncomfortably with the views of audit committee members - in line with regulation - that theirs is an oversight function. Although audit committee practices differ widely, they appear to evolve to suit the companies' and individuals' particular contexts. Accordingly, legislation to standardise practice might not be useful, indeed, it may be counter productive. Given the potential changes to UK regulation that could arise from implementing the EU 8th Directive, it is important that this point be made explicitly to legislator